2011
DOI: 10.3168/jds.2011-4187
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the influence of variation factors on electrical conductivity of milk in Murciano-Granadina goats

Abstract: The aim of this study was to obtain further knowledge on electrical conductivity (EC) of milk as a tool for detecting mastitis in goats. The effect of farm, parity, stage of lactation, and health status of the glands on EC, and the somatic cell count (SCC) of milk was analyzed. Additionally, relationships between EC and chemical composition and SCC were studied. Finally, characteristics of EC and SCC (sensitivity and specificity) as diagnostic tests used to detect mastitis were studied. One hundred and five Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
41
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 17 publications
(23 reference statements)
14
41
5
Order By: Relevance
“…Tangorra et al (2010) found a significantly higher level of EC in infected glands, but only in different lactation stages (LSs) and types of EC traits. Diaz et al (2011) observed a remarkable effect with unspecific mastitis (negative bacterial culture and SCC>1,000,000 cells/mL), which they related to EC variations arising from other factors, such as farm, parity, month of lactation, and milk composition. In another study based on daily EC measurements , a remarkable increase in EC was observed, when major pathogens were causing an infection.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Tangorra et al (2010) found a significantly higher level of EC in infected glands, but only in different lactation stages (LSs) and types of EC traits. Diaz et al (2011) observed a remarkable effect with unspecific mastitis (negative bacterial culture and SCC>1,000,000 cells/mL), which they related to EC variations arising from other factors, such as farm, parity, month of lactation, and milk composition. In another study based on daily EC measurements , a remarkable increase in EC was observed, when major pathogens were causing an infection.…”
Section: Introductionmentioning
confidence: 91%
“…CE n 1662/2006 sets at 1,500,000 cells/mL the legal limit for somatic cells in raw goat milk, whereas this limit was set at 1,000,000 cells/mL according to the Pasteurized Milk Ordinance regulation (FDA, 2007). In the literature, some recent studies on dairy goats (Diaz et al, 2011(Diaz et al, , 2012 reported that the persistence of 1,000,000 somatic cells/mL which is not due to physiological causes is indicative of nonhealthy glands, even if bacteriological analysis are negative for IMI. In the present study, the threshold of SSC was selected being the lower level among those reported above.…”
Section: Collection and Analyses Of Milk Samplesmentioning
confidence: 99%
“…To determine the health status of the glands, both bacteriological analysis and SCC results were considered in addition to clinical observation, according to Diaz et al (2011). A gland was defined as having bacterial mastitis (positive for IMI) when bacteriological analyses were positive.…”
Section: Experimental Design and Analyzed Variablesmentioning
confidence: 99%
“…There are several factors other than mastitis related to EC, including differences between animals, so that, in dairy cows, methods that employ an absolute EC threshold for all the animals for mastitis detection are not accepted, even if EC is measured in the complete milking or at gland level. Studies in dairy goats (Ying et al 2002;Diaz et al, 2011Diaz et al, , 2012Romero et al 2012) have shown significant effects of parity, lactation stage, farm, and the analyzed fraction, in addition to mammary infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation